Pengaruh Self Assessment System dan Kualitas Pelayanan Pajak terhadap Kepatuhan Wajib Pajak di KPP Pratama Garut - lina nurlaela (Fakultas Ekonomi Universitas Garut, 2018)
This study aims to determine the Self Assessment System, Quality of Tax Service, and Taxpayer Compliance at KPP Pratama Garut. As well as to determine the effect of the Self Assessment System and the Quality of Tax Services on Taxpayer Compliance at Garut Tax Office. The method used in this research is descriptive and associative methods. The population of this research is individual taxpayers who are registered as taxpayers at KPP Pratama Garut. The sample used in this study were 100 respondents. Hypothesis testing in this study used multiple linear regression with an alpha value of 5%. The results of this study indicate that the Self Assessment System at KPP Pratama Garut is good, the Quality of Tax Service at KPP Pratama Garut shows good, and Taxpayer Compliance at KPP Pratama Garut Regency also shows good. Self Assessment System and Tax Service Quality have a positive effect on Taxpayer Compliance at KPP Pratama Garut Regency. The magnitude of the influence of the Self Assessment System and the Quality of Tax Services has a positive effect on Taxpayer Compliance is 75.8%.